Pengaruh NPM, CR, dan EPS Terhadap Harga Saham di JII70 Periode 2019-2023 - Evan Erlando; Trisnadi Wijaya (MDP Student Conference, 2026)
This study aims to examine how Net Profit Margin (NPM), Current Ratio (CR), and Earning Per Share (EPS) affect the stock prices of companies listed on the Jakarta Islamic Index 70 (JII70) during the period from 2019 to 2023. Using a quantitative associative approach, data were collected from 39 companies using purposive sampling, resulting in 195 observations. Data analysis was performed using multiple linear regression method through SPSS version 26 software. The results of the F test (simultaneous) showed that the F-statistic value of 11.385 is greater than the F-table value of 2.27 with a significance level of 0.000, which is less than 0.05. This indicates that NPM, CR, and EPS simultaneously have a significant effect on stock prices. Partially, the results of the t-test indicate that EPS negatively and significantly affects stock prices, while NPM and CR do not have a significant impact on stock prices. The coefficient of determination (Adjusted ) of 0.229 indicates that 22.9% of the changes in stock prices are explained by the three variables studied, while 77.1% are influenced by other factors not included in this study.